Scoping review on Physical Health Conditions in Irish Travellers (Mincéiri) - David Mockler; Julie Broderick; Fiona Kennedy; Amy Ward; Jacopo Villani (BMJ Open)
Objective The objective of this scoping review was to collate physical health conditions in Mincéiri—Irish Travellers.Design Scoping review.Search strategy and charting method MEDLINE/PubMed, EMBASE, PEDro, AMED, CINAHL, PsycINFO, SCOPUS as well as reports and grey literature were searched for primary data reporting physical health conditions of Irish Travellers up to 4 April 2023. Data was extracted, described and organised meaningfully into tables according to reported physical health conditions.Eligibility criteria The population was Travellers. The concept referred to physical health conditions. The context was Irish Travellers based in any location or setting. Exclusion criteria was data/research other than primary data relating to physical health conditions of Irish Travellers.Results From 198 citations generated from the database search, 11 unique studies (20 reports) were included in this scoping review, including n=7397 participants. Driven by the data, physical health conditions were categorised into cardiovascular diseases, respiratory diseases, injuries/musculoskeletal/arthritic disorders, genetic disorders and gut/bowel conditions. This review showed that the metabolic syndrome, asthma, bronchitis, tuberculosis and intentional injuries were 2–3 times more prevalent in Irish Travellers compared with the background population. Genetic conditions were also described in a proportion of Travellers.Conclusions Overall, Irish Travellers experience a disproportionate burden of physical health conditions compared with background populations. Healthcare providers need to be aware of the unique physical health burden experienced by many Irish Travellers. Multifaceted strategies are needed to improve the health profile of this vulnerable and marginalised group.